2016
DOI: 10.1186/s12986-016-0113-y
|View full text |Cite|
|
Sign up to set email alerts
|

Modified Atkins diet in advanced malignancies - final results of a safety and feasibility trial within the Veterans Affairs Pittsburgh Healthcare System

Abstract: BackgroundDysfunctional mitochondrial processes limit malignant cells ability to use energy from fatty acids and ketones. Animal studies using ketogenic diets for cancer show encouraging results. We tested the diet’s safety and feasibility in cancer patients across a broad variety of solid tumors.MethodsWe recruited 17 advanced cancer patients who were not on chemotherapy. They consumed 20 to 40 g of carbohydrates daily with evaluations performed weekly until week 4, then every 4 weeks until 16 weeks. Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 28 publications
(34 reference statements)
3
89
2
3
Order By: Relevance
“…Seven studies reported on changes in blood lipids. Four studies did not observe any significant changes in triglycerides, cholesterol, high‐density lipoprotein and low‐density lipoprotein . One study reported a significant drop in low‐density lipoprotein and high‐density lipoprotein .…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Seven studies reported on changes in blood lipids. Four studies did not observe any significant changes in triglycerides, cholesterol, high‐density lipoprotein and low‐density lipoprotein . One study reported a significant drop in low‐density lipoprotein and high‐density lipoprotein .…”
Section: Resultsmentioning
confidence: 90%
“…All studies investigated the effect of oral KD; however, there was considerable variation in how the diet was delivered. Three studies followed a traditional KD with a 4 : 1 or 3 : 1 fat (F) to carbohydrate CHO) + protein (P) kg m –2 (F : CHO + P) , two studies used a ratio of F : CHO + P between 0.7 : 1 and 1.8 : 1 , three studies used a modified Atkins diet (20–40 g day −1 CHO) , two studies used a low glycaemic index diet (<70 g day −1 CHO) and one study used a Paleolithic KD with a F : P ratio of 2 : 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations